Rancang Bangun Aplikasi Mobile Tracking Dengan Menggunakan Sms Gateway Untuk Meningkatkan Keamanan Pada PT. ARTIDUTA ANEKA USAHA - Sandana, I Putu Dedy; Wibowo, Januar; Taufik, Vicky M (Jurnal JSIKA, 2012)
Car thefts lately very prevalent both intensity and location of events that makes PT. Meaning of Various Business Ambassadors become restless for delivery of goods. In general, only the form of car security alarm installation and assembly has been widely known existence. While it never developed a tracking system and vehicle safety position, which can be accessed online and can not be monitored by cell phone or mobile phones (HP) as it also requires a monthly fee for the expenditure rates can make the monitoring of vehicles that have been provided by several companies that providing mobile tracking service. PT. Various meanings Ambassador Enterprises need a tool and application that can monitor the vehicle position and disable the ignition remotely. Then designed and built a Car Security System Based Geographic Information Systems, Car Security System for which it can monitor the vehicle remotely and provide a sense of security on the company´s automobile operations. The system is based Geographic Information System (GIS) where the system that include a map to determine the existence of such vehicles are seen on the map using the Google Maps API. Key words: mobile tracking, sms gateway, security